Proceedings of the Seventh International Workshop on Variability Modelling of Software-Intensive Systems 2013
DOI: 10.1145/2430502.2430513
|View full text |Cite
|
Sign up to set email alerts
|

A survey of variability modeling in industrial practice

Abstract: Over more than two decades, numerous variability modeling techniques have been introduced in academia and industry. However, little is known about the actual use of these techniques. While dozens of experience reports on software product line engineering exist, only very few focus on variability modeling. This lack of empirical data threatens the validity of existing techniques, and hinders their improvement. As part of our effort to improve empirical understanding of variability modeling, we present the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
206
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 333 publications
(212 citation statements)
references
References 27 publications
4
206
0
2
Order By: Relevance
“…As demonstrated by the ERP example and confirmed by the literature [19,20,21,19], companies currently are employing diverse solutions for modeling variability and supporting product configuration. For the configuration of a common product in such a context, an integrative infrastructure is needed, which works on concepts shared among the different modeling notations.…”
Section: Motivating Example and Discussion Of Requirementsmentioning
confidence: 93%
“…As demonstrated by the ERP example and confirmed by the literature [19,20,21,19], companies currently are employing diverse solutions for modeling variability and supporting product configuration. For the configuration of a common product in such a context, an integrative infrastructure is needed, which works on concepts shared among the different modeling notations.…”
Section: Motivating Example and Discussion Of Requirementsmentioning
confidence: 93%
“…We previously surveyed companies in their use of variability modeling [5] and conducted semi-structured interviews with eight of them. In the present work, we select three companies and describe and analyze them in-depth.…”
Section: -What Are the Benefits (Rq2) And What Are The Challenges (Rqmentioning
confidence: 99%
“…In the present work, we select three companies and describe and analyze them in-depth. Our selection represents a broad range of development scales from very small (two developers) to ultra-large (100 development teams); comprises domains that commonly use variability modeling (automotive, industrial applications/energy, and eCommerce [5]); and covers all product-line adoption strategies (proactive, extractive, and reactive [27]). In contrast to quantitative research, our goal is not too reach any statistically significant deductions, but to describe the practices that were successful in three heterogeneous cases.…”
Section: -What Are the Benefits (Rq2) And What Are The Challenges (Rqmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent survey of variability modeling showed that FMs are by far the most frequently reported notation in industry [28].…”
Section: Introductionmentioning
confidence: 99%